2020
DOI: 10.1159/000511157
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Resection versus Re-Ablation for Intrahepatic Recurrent Hepatocellular Carcinoma after Initial Ablation Therapy

Abstract: <b><i>Background and Aims:</i></b> Whether surgical resection or repeated ablation should be recommended for intrahepatic recurrent hepatocellular carcinoma (HCC) conforming to the Milan criteria after initial ablation remains unclear. In this study, we compared the outcomes of patients who underwent surgical resection with those who underwent re-ablation for recurrent HCC after initial curative-intent ablation. <b><i>Methods:</i></b> The data of 28 and 98 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…The HR data from 14 studies ( 10 12 , 16 18 , 27 , 28 , 31 33 , 35 , 37 , 38 ) on RFS were included for meta-analysis. Given the low heterogeneity among the study groups (I 2 = 0%), a fixed effect model was employed for data integration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The HR data from 14 studies ( 10 12 , 16 18 , 27 , 28 , 31 33 , 35 , 37 , 38 ) on RFS were included for meta-analysis. Given the low heterogeneity among the study groups (I 2 = 0%), a fixed effect model was employed for data integration.…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies (12,16,18,25,31,32,(35)(36)(37)(38) provided data on severe postoperative complications (Clavien-Dindo grade III or higher).The incidence of severe postoperative complications was 11.4% (88/769) in the RH group and 3.6% (31/860) in the TAT group. The heterogeneity of these trials was moderate (I 2 = 53%); therefore, a random effects model was employed to pool data.…”
Section: Postoperative Complications and Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Manual screening revealed two studies which reported on survival after repeat TA following primary TA [13,14]. Both were performed in Asian populations, with comparatively young patients (median age 50 [13], and 60 [14]), with almost exclusively viral hepatitis-induced HCC. One study reported a number of non-cirrhotic patients above 30% [13].…”
Section: Discussionmentioning
confidence: 99%